A novel composite vibration control method using double-decked floating raft isolation system and particle damper. (October 2018) - Lei, Xiaofei; Wu, Chengjun; Wu, Hengliang
This paper presents a composite vibration control method that uses a double-decked floating raft isolation system and particle dampers to control the severe vibration of a heavy compressor set. In view of the structural characteristics of the compressor set, a mechanical impedance method is employed to investigate the acceleration transfer ratios of the double-decked floating raft isolation system, and to design three isolating schemes. Numerical results indicate that the particle damping technology does not disturb the isolating performance of the double-decked floating raft isolation system while reducing only its acceleration amplitude. To improve the damping performance of particle dampers, an anti-resonance method and a co-simulation technique are used to optimize the installation location of the particle dampers, as the damping effect is related to the vibrating velocity at the damper's position. Furthermore, two types of particle damper—cylindrical and cuboid—are designed, based on conclusions drawn from experiments using the anti-resonance method. The damping effectiveness of the particle damper scheme is also examined using the co-simulation technique; results indicate that the proposed installation scheme can effectively suppress the vibration of the compressor rack. In addition, the presented schemes using the composite vibration control method are verified and compared in on-site experiments, and results demonstrate that the third isolating scheme presented, combined with particle damping technology, is best in controlling vibration of the compressor set.